Returns to education during and after the economic crisis: Evidence from Latvia 2006-2012 - Karlis Vilerts; Olegs Krasnopjorovs; Edgars Brekis (Comparative Economic Research. Central and Eastern Europe, 2017)
We employ EU-SILC micro data for Latvia to study how returns to education changed during the economic crisis of 2008-2009 and afterwards. We found that returns to education increased significantly during the crisis and decreased slightly during the subsequent economic recovery. The counter-cyclical effect was evident in nearly all population groups. After the crisis, education became more associated than before with a longer working week and a higher employment probability. Furthermore, we show that returns to education in Latvia are generally higher in the capital city and its suburbs than outside the capital city region, as well as for citizens of Latvia than for resident non-citizens and citizens of other countries, but lower for males and young people. Wage differential models reveal a relatively large wage premium for higher education and a rather small one for secondary education. Estimates obtained with instrumental variable (IV) models significantly exceed the OLS estimates.
Keywords: 330; returns to education; Mincer coefficient; wage differentials model; higher education wage premium; instrumental variables